Long terminal repeats power evolution of genes and gene expression programs in mammalian oocytes and zygotes - Franke, Vedran; Ganesh, Sravya; Karlic, Rosa; Malik, Radek; Pasulka, Josef; Horvat, Filip; Kuzman, Maja; Fulka, Helena; Cernohorska, Marketa; Urbanova, Jana; Svobodova, Eliska; Ma, Jun; et al. (Genome research, 2017)
Retrotransposons are "copy-and-paste" insertional mutagens that substantially contribute to mammalian genome content. Retrotransposons often carry long terminal repeats (LTRs) for retrovirus-like reverse transcription and integration into the genome. We report an extraordinary impact of a group of LTRs from the mammalian endogenous retrovirus-related ERVL retrotransposon class on gene expression in the germline and beyond. In mouse, we identified more than 800 LTRs from ORR1, MT, MT2, and MLT families, which resemble mobile gene-remodeling platforms that supply promoters and first exons. The LTR-mediated gene remodeling also extends to hamster, human, and bovine oocytes. The LTRs function in a stage-specific manner during the oocyte-to-embryo transition by activating transcription, altering protein-coding sequences, producing noncoding RNAs, and even supporting evolution of new protein-coding genes. These functions result, for example, in recycling processed pseudogenes into mRNAs or lncRNAs with regulatory roles. The functional potential of the studied LTRs is even higher, because we show that dormant LTR promoter activity can rescue loss of an essential upstream promoter. We also report a novel protein-coding gene evolution-D6Ertd527e-in which an MT LTR provided a promoter and the 5' exon with a functional start codon while the bulk of the protein-coding sequence evolved through a CAG repeat expansion. Altogether, ERVL LTRs provide molecular mechanisms for stochastically scanning, rewiring, and recycling genetic information on an extraordinary scale. ERVL LTRs thus offer means for a comprehensive survey of the genome's expression potential, tightly intertwining with gene expression and evolution in the germline.
Keywords: genetická transkripce; endogenní retroviry; molekulární evoluce; křečci praví; retroelementy; Humans; Endogenous Retroviruses; Promoter Regions, Genetic; Zygote; regulace genové exprese; Evolution, Molecular; Transcription, Genetic; zygota; lidé; Terminal Repeat Sequences; zvířata; myši; Retroelements; Mice; oocyty; Cattle; Gene Expression Regulation; skot; koncové repetice; Cricetinae; Animals; Oocytes; promotorové oblasti (genetika)